Perioperative Factors Contributing the Post-Craniotomy Pain: A Synthesis of Concepts - Chowdhury, Tumul; Garg, Rakesh; Sheshadri, Veena; Venkatraghavan, Lakshmi; Bergese, Sergio Daniel; Cappellani, Ronald B.; Schaller, Bernhard (Frontiers in Medicine, 2017)
The perioperative management of post-craniotomy pain is controversial. Although the concept of pain control in non-neurosurgical fields has grown substantially, the understanding of neurosurgical pain and its causative factors in such a population is inconclusive. In fact, the organ that is the center of pain and its related mechanisms receives little attention to alleviate distress during neurosurgical procedures. In contrast to the old belief that pain following intracranial surgery is minimal, recent data suggest the exact opposite. Despite the evolution of various multimodal analgesic techniques for optimal pain control, the concern of post-craniotomy pain remains. This paradox could be due to the lack of thorough understanding of different perioperative factors that can influence the incidence and intensity of pain in post-craniotomy population. Therefore, this review aims to give an in-depth insight into the various aspects of pain and its related factors in adult neurosurgical patients.